PATTERNS OF RIFAMPICIN AND ISONIAZID RESISTANCE IN PULMONARY RR/MDR-TB WITH OR WITHOUT T2DM - Sopha, May Ira; Wulandari, Laksmi; Rusli, Musofa; Husada, Dominicus; Prodjosoewojo, Susantina (Folia Medica Indonesiana, 2025)
Tuberculosis (TB) causes approximately[-12pc]AU: Please provide ORCID ID for all authors. 1.6 million deaths each year. The incidence of drug-resistant TB has continued to rise, primarily due to multidrug-resistant tuberculosis (MDR-TB). Drug-resistant TB remains a primary concern in various parts of the world, especially in Eastern Europe, Russia, Asia, and sub-Saharan Africa. This study aimed to analyze the correlation between first-line anti-tuberculosis drug resistance and the presence or absence of T2DM comorbidity in patients with pulmonary RR/MDR TB. This research employed a cross-sectional design, which used secondary data from 2023, obtained from medical records, the Tuberculosis Information System (SITB), and the results of first-line DST tests. The subjects included the RR-TB or MDR-TB patients with or without T2DM, treated at the MDR-TB outpatient clinic of Dr. Soetomo General Hospital, Surabaya. Of 131 patients, a portion had T2DM comorbidity. Statistical analysis showed no significant association between T2DM status and individual resistance to rifampicin (p = 0.247) or isoniazid (p = 0.312). However, clinically, patients with T2DM tended to exhibit more severe and complex resistance patterns. Although there was no statistically significant relationship between T2DM and first-line drug resistance, the presence of T2DM clinically indicated a tendency toward more severe resistance profiles.